ANALISA DAMPAK PEMBERDAYAAN KELUARGA MISKIN MELALUI BANTUAN SOSIAL TERHADAP KESEJAHTERAAN DI KECAMATAN PAYAKUMBUH SELATAN KOTA PAYAKUMBUH - Rina Deswita; Ria Ariany (Journal Publicuho, 2024)
The purpose of this study was to analyze the strategy and impact of the implementation of community empowerment as well as the effect of social assistance on improving the welfare of poor families in Payakumbuh Selatan Sub-district, Payakumbuh City. Data collection was conducted through semi-structured interviews. Data analysis was carried out using triangulation techniques. The results of the study found that the Regional Apparatus has provided assistance in the form of productive economic business development facilities for the extremely poor and the poor in the data on the Acceleration of Targeting for Extreme Poverty Reduction (P3KE). In addition, the budget was also increased through fiscal incentives to conduct skills training and empower the poor. As a result, the poor in Payakumbuh Selatan Sub-district have received assistance for business capital. For the vulnerable, such as people with disabilities and the elderly, social protection and security assistance are provided, such as the National Health Insurance (JKN), the Family Hope Program (PKH), and rice groceries. There are several factors that hinder the running of the empowerment program, such as inadequate facilities and infrastructure, not yet mapping the potential and abilities of poor families who will be optimally empowered, and the personal mentality of the poor themselves.